أثر مقاومة التغيير على كفاءة أداء المنظمة دراسة ميدانية على العاملين في مجلس مدينة اللاذقية - اليوسفي, أحمد; درويش, رامز علي (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يهدف البحث إلى دراسة أثر مقاومة العاملين للتغيير على كفاءة أداء المنظمة المتمثلة بمجلس مدينة اللاذقية والمديريات التابعة له. ودراسة الفروق بين العاملين في مقاومتهم للتغيير تبعاً لمتغيرات الجنس, والعمر, والخبرة, والمؤهل العلمي. استخدم الباحث المنهج الوصفي التحليلي, وشمل مجتمع البحث جميع العاملين في مديريات مجلس اللاذقية والبالغ عددهم (3160) عامل, وبلغ حجم العينة من العاملين (343) عامل تمّ توزيع الاستمارات عليهم, وأعيد منهم (331) استمارة كاملة وصالحة للتحليل الإحصائي, وبنسبة استجابة بلغت (96.5%). وكان من أهم نتائج البحث: 1- يقاوم العاملون في مديريات مجلس مدينة اللاذقية التغيير, ويظهر ذلك من خلال معارضتهم القوانين الجديدة التي لا تخدمهم, وبحثهم عن مكتسبات شخصية بغض النظر عن النتائج, وتفضيلهم العمل الروتيني, وإنجازهم لأعمالهم ببطء, وعدم طرحهم أفكار جديدة منذ زمن بعيد. 2- هناك علاقة ارتباط متينة وعكسية بين مقاومة العاملين للتغيير وكفاءة أداء المنظمة, أي كلما ازدادت مقاومة العاملين للتغيير انخفضت كفاءة أداء المنظمة, حيث أن (64.8%) من التباين الحاصل في كفاءة أداء المنظمة يفسره مقاومة العاملين للتغيير, والباقي يعزى لأسباب أخرى. 3- عدم وجود فروق دالة إحصائياً بين متوسطات إجابات العاملين في مقاومتهم للتغيير تبعاً للخصائص الشخصية (الجنس, الخبرة, العمر, المؤهل العلمي). The research aims to study the impact resistance of employees to change the efficiency of the performance of the organization of Lattakia City Council and the relevant directorates. It studies the differences between working in their resistance to change depending on the variables of gender, age, experience, and qualifications. The researcher adopts the descriptive analytical method. The research community includes all employees in the departments of the Council of Lattakia's (3160) factor, with a sample size of (343) workers, to whom forms were distributed. (331) forms returned as complete and valid for statistical analysis, and response rated (96.5%). The most important results: 1. Workers in the departments of the Lattakia City Council resist change, it appears that through their opposition to the new laws that do not serve them, their search for the gains of character, regardless of the results, a preference for routine work, the achievement of their business slowly, and not cast them new ideas a long time ago. 2. There is a strong correlation between resistance and counter-productive workers to change the performance and efficiency of the organization, i.e., the greater the resistance to change as workers decreased efficiency of the performance of the organization, where that (64.8%) of the discrepancy in the efficiency of the organization's performance is explained by staff resistance to change. 3. The lack of statistically significant differences between the mean answers workers in their resistance to change depending on the personal characteristics (sex, experience, age, academic qualification). أثر مقاومة التغيير على كفاءة أداء المنظمة دراسة ميدانية على العاملين في مجلس مدينة اللاذقية